Team interventions in acute hospital contexts: a systematic search of the literature using realist synthesis - U. Cunningham; M. E. Ward; A. De Brún; E. McAuliffe (BMC, 2018)
Abstract Background Research on team effectiveness in healthcare has focussed on whether effective teams yield positive outcomes for patients and on the effectiveness of team interventions to improve performance. Limited understanding exists of what works for whom within an effective team, or how and why the context in which the team operates enables team members both as individuals and as a collective to enact behaviours that promote positive outcomes. Methods This realist synthesis of the literature explores the relationship between team interventions, underlying teamwork mechanisms generated by those interventions, and the resultant impact on patient outcomes in an acute hospital context. A systematic search of five healthcare and healthcare management academic databases: PubMed, PsychINFO, CINAHL, ABInform, Emerald Management and three grey literature databases: ERIC, OpenDOAR and Open Grey was undertaken. Five experts in the field were also contacted to source relevant literature. Using PRISMA guidelines, relevant studies published between January 2006 and January 2017 were systematically searched by a team of three people. Drawing on realist methodology, data were synthesised using context, mechanism and outcome configurations as the unit of analysis to identify enablers and barriers to effective team interventions. Results Out of 3347 papers retrieved, 18 were included in the final synthesis. From these, five contextual enablers were identified: an inter-disciplinary focus and flattened hierarchy; effective communication; leadership support and alignment of team goals with organisational goals; credibility of intervention; and appropriate team composition with physician involvement. Ten recurring mechanisms were identified, the most frequently occurring of which was shared responsibility. Conclusions The advantage of using realist synthesis to extrapolate data from the literature is that it considers the context and mechanisms that will impact effectiveness of healthcare team interventions. This methodological approach provides a different perspective to other types of syntheses and offers insight as to why certain contextual elements may yield more success than others. Findings therefore tend to have more practical implications. Specificity of detail in terms of how external drivers impact on healthcare team interventions was limited in the articles extracted for analysis. This broader perspective is therefore an important consideration for future research.